Novel Materials and Advanced Characterization for Energy Storage and Conversion - Qingyuan Li; Jen-Hung Fang; Wenyuan Li; Xingbo Liu (Energies, 2022)
Global climate changes, such as frequent extreme weather, continuous temperature increase, and melting glaciers, constantly press us to reduce our dependence on the traditional carbon-based energy resources [...]